Sedentary behavior after stroke: A new target for therapeutic intervention. Issue 1 (January 2019) - Morton, Sarah; Fitzsimons, Claire; Hall, Jennifer; Clarke, David; Forster, Anne; English, Coralie; Chastin, Sebastien; Birch, Karen M; Mead, Gillian
Over the last 10 years, evidence has emerged that too much sedentary time (e.g. time spent sitting down) has adverse effects on health, including an increased risk of cardiovascular disease incidence and mortality. A considerable amount of media attention has been given to the topic. The current UK activity guidelines recommend that all adults should minimize the amount of time spent being sedentary for extended periods. How best to minimize sedentary behavior is a focus of ongoing research. Understanding the impact of sedentary behaviors on the health of people with stroke is vital as they are some of the most sedentary individuals in society. Implementing strategies to encourage regular, short breaks in sedentary behaviors has potential to improve health outcomes after stroke. Intervention work already conducted with adults and older adults suggests that sedentary behaviors can be changed. A research priority is to explore the determinants of sedentary behavior in people with stroke and to develop tailored interventions.